Analisis Tektonik Relatif Menggunakan Metode Morfotektonik Daerah Lintau Buo dan Sekitarnya, Tanah Datar, Sumatera Barat - Putri, Atika Nabila; Setiawan, Budhi (Journal of Applied Geoscience and Engineering, 2023)
The area of this research is in the Lintau Buo Region, Tanah Datar District, West Sumatra. Based on the regional geology, the location is on the boundary of the Ombilin Basin which has active tectonic conditions. This research is to get data of tectonic levels using a quantitative geomorphological approach carried out in the Batang Sinamar sub-watershed and the Batang Tampo sub-watershed. Some of the parameters used for this study include Drainage Density (Dd), Bifurcation Ratio (Rb), Hypsometric Integral (HI), Valley Floor Width and Height Ratio (Vf), Mountain Front Sinousity (Smf), and Asymmetry Factor (AF). And then the outcome of the parameters compared using IAT (Index of Active Tectonic) analysis. The results of the calculation are obtained with segment 1 entering class 3, namely moderate tectonics, and segments 2 and 3 entering class 2, namely high tectonics. The drainage pattern of the river at this research location is a pararellel drainage pattern which is controlled by geological structures such as folds. The results calculation of the IAT analysis is the landform of the morphology research location is controlled by moderate to high levels of tectonic activity and produces various denudational and erosional processes that cause soil movement and landslides.